Optimizing Local Chicken Productivity in a Semi-Intensive System in the Sepakat Jaya Livestock Group, Padang Laweh Village, Kampar District - Sadarman, Sadarman; Misrianti, Restu; Ahmad, Zuri; Novianti, Sri; Handoko, Jully (Journal of Animal Nutrition and Production Science, 2023)
The productivity of local chickens can be improved through the enhancement of the rearing system, ranging from extensive to intensive management. This research aims to identify the production characteristics of native chickens reared semi-intensively in the Sepakat Jaya Livestock Group, Padang Laweh Village. Ten farmers who raise more than 20 local chickens were selected as respondents for this study. The research was conducted in the form of a survey, with the selection of the location, farmers as respondents, and the use of native chickens as research samples carried out through purposive sampling. The collected data, such as the age at first egg laying, the body weight of the hens at first egg laying, and the weight of the first egg, were analyzed using descriptive statistics. The results of this study indicate that the production characteristics of local chickens reared semi-intensively in the Sepakat Jaya, Padang Laweh, include age at first egg laying of approximately 178.7 days, a body weight of hens at first egg laying of around 1.46 kg per bird, and a weight of the first egg of about 49.1 grams per egg. This research concludes that semi-intensive rearing can improve the production characteristics of local chickens in the Sepakat Jaya, Padang Laweh.